Dampak Berbagi Pengetahuan terhadap Kinerja Karyawan yang Dipengaruhi oleh Kepuasan Kerja pada Divisi Akuntansi dan Keuangan PT XYZ, Tbk. - Tinjung Desy Nursanti; Willy Natan; Indah Syah Pratiwi Siregar; Raymond Putra Edfran (Jurnal Ekonomi, Manajemen dan Perbankan (Journal of Economics, Management and Banking), 2018)
In the business process the company must be able to understand and implement its owned assets and one of the important resources is its human resources to be able to utilize its human resources well, employee performance can be supported with various other resources with strategic efforts, such as paying attention to how employee satisfaction level and employee desire in sharing knowledge. So the purpose of this study is to determine the effect of job satisfaction on knowledge sharing and its impact on employee performance of the Finance and Accounting department of PT XYZ Tbk. With data collection techniques through questionnaires given to employees and then data processed with SPSS 22 software using Path Analysis method, obtained the result that job satisfaction has an influence on knowledge sharing, and then knowledge sharing has an influence on employee performance. Job satisfaction is influenced by the satisfaction of salary and how attractive the work, knowledge sharing influenced by the desire to discuss and information obtained by employees, and employee performance is influenced by attitude and knowledge about the job.